EFFECTIVENESS OF MARKETING TOOLS IN A COMPETITIVE BUSINESS ENVIRONMENT - Сінельнікова, Наталія (SWorldJournal, 2025)
The article focuses on analyzing the effectiveness of modern marketing tools within the context of business operations in a competitive environment. The purpose of the article is to justify the role of innovative marketing tools in building sustainable co